Pengaruh Kinerja Lingkungan, Biaya Lingkungan, Dan Ukuran Perusahaan Terhadap Kinerja Keuangan - Ananda, Riri Gusnia; Hendrawaty, Ernie (Goodwood Publishing, 2025)
This study seeks to analyze the impact of environmental performance, environmental expenses, and company size on the financial performance of food and beverage firms listed on the Indonesia Stock Exchange from 2018 to 2022. The study utilized multiple linear regression analysis on a sample of 100 data points from 20 firms. The findings indicate that environmental performance adversely and significantly impacts financial performance, suggesting that enhancements in environmental performance diminish firm profitability. Environmental expenses adversely and significantly impact financial performance, indicating that increased environmental expenditures have not yielded commensurate financial rewards. Simultaneously, business size exerts a positive and considerable influence on financial performance, indicating that organizations with greater assets are more adept at generating profits. This study underscores the significance of efficient environmental cost management systems and the necessity of reconciling environmental social responsibility with business financial objectives. Moreover, larger enterprises possess enhanced chances to retain stability and improve their performance in response to the escalating demands for sustainable business practices.